Two kinds of ferritin protect ixodid ticks from iron overload and consequent oxidative stress. - Remil Linggatong Galay; Rika Umemiya-Shirafuji; Eugene T Bacolod; Hiroki Maeda; Kodai Kusakisako; Jiro Koyama; Naotoshi Tsuji; Masami Mochizuki; Kozo Fujisaki; Tetsuya Tanaka (PLoS ONE)
Ticks are obligate hematophagous parasites that have successfully developed counteractive means against their hosts' immune and hemostatic mechanisms, but their ability to cope with potentially toxic molecules in the blood remains unclear. Iron is important in various physiological processes but can be toxic to living cells when in excess. We previously reported that the hard tick Haemaphysalis longicornis has an intracellular (HlFER1) and a secretory (HlFER2) ferritin, and both are crucial in successful blood feeding and reproduction. Ferritin gene silencing by RNA interference caused reduced feeding capacity, low body weight and high mortality after blood meal, decreased fecundity and morphological abnormalities in the midgut cells. Similar findings were also previously reported after silencing of ferritin genes in another hard tick, Ixodes ricinus. Here we demonstrated the role of ferritin in protecting the hard ticks from oxidative stress. Evaluation of oxidative stress in Hlfer-silenced ticks was performed after blood feeding or injection of ferric ammonium citrate (FAC) through detection of the lipid peroxidation product, malondialdehyde (MDA) and protein oxidation product, protein carbonyl. FAC injection in Hlfer-silenced ticks resulted in high mortality. Higher levels of MDA and protein carbonyl were detected in Hlfer-silenced ticks compared to Luciferase-injected (control) ticks both after blood feeding and FAC injection. Ferric iron accumulation demonstrated by increased staining on native HlFER was observed from 72 h after iron injection in both the whole tick and the midgut. Furthermore, weak iron staining was observed after Hlfer knockdown. Taken together, these results show that tick ferritins are crucial antioxidant molecules that protect the hard tick from iron-mediated oxidative stress during blood feeding.